Swells over the Arabian Sea during the months, May, June and July - THIRUVENGADATHAN, A.; PADVAL, S. V.; SINGH, R. S. (MAUSAM, 1984)
The paper presents the climatological features of the swells over the Arabian Sea, based on the observations made by the Russian research vessels during the Indo-Soviet Monsoon Experiment (ISMEX) 1973, Monsoon Experiment 1977 and Monex 1979.